Interlayer Defect Effects on the Phonon Properties of Bilayer Graphene and its Nanoribbon - Anindya, Khalid (Université d'Ottawa / University of Ottawa, 2020)
Phonon properties of AB (Bernal) stacked bilayer graphene (BLG) with various types of defects have been investigated theoretically. Forced Vibrational (FV) method has been employed to compute the phonon modes of disordered BLG. A downward linear shift of E2g mode frequencies has been observed with an increasing amount of defect concentration. Moreover, two identical E2g peaks have been observed in PDOS of the bilayer system where the individual layer contains 12C and 13C atoms respectively. From computed typical mode patterns of in-plane K-point optical mode phonons, it has been noticed that phonons become strongly localized around a few nanometers area at the presence of defects and localized modes increase with the increasing amount of defect concentration. The edge effect on the localized phonon modes has also been discussed for bilayer armchair graphene nanoribbons (BiAGNRs). The impact of defects on the phonon conduction properties has also been studied for BiAGNRs. My investigated results can be convenient to study the thermal conductivity and electron-phonon interaction of bilayer graphene-based nanodevices and to interpret the Raman and infrared spectra of disordered system.
Keywords: Bilayer; Graphene; Nanoribbon; Phonon; Vibrational properties